Eco-Heart Index as a tool for community-based water quality monitoring and assessment - Sakai, Nobumitsu; Mohamad, Zeeda Fatimah; Nasaruddin, Affan; Abd Kadir, Siti Norasiah; Mohd Salleh, Mohammad Shahrul Amin; Sulaiman, Abdul Halim (Elsevier, 2018)
This study aimed to develop an economical, user-friendly, policy-relevant and impactful community-based water quality monitoring and assessment tool called Eco-Heart Index. Simple and economical water quality monitoring tools, such as Pact Test and LAQUAtwin, were used for Eco-Heart Index. The data was validated by comparing with those obtained using standard methods. Eco-Heart Index is a novel water quality indicator that draws a heart shape based on a result of 6 water quality parameters (pH, heavy metals, chemical oxygen demand, transparency, ammonia nitrogen and dissolved oxygen), which then indicates the water quality (i.e., a full heart stands for clean water, while a broken heart stands for polluted water). This simplified tool was applied to the Langat River basin in Malaysia to generate a water quality map and to categorize the pollution trend based on the drawn figures. The water quality map showing the results of Eco-Heart Index clearly visualized the occurrence and distribution of the water pollution in the whole river basin. Specifically, a full heart shape appeared in upstream areas, whereas various broken heart shapes appeared in mid-stream and downstream areas, particularly in populated and land development areas. Eco-Heart Index was strongly correlated with the National Water Quality Index for Malaysia, suggesting that it could also be utilized as an alternative tool for water quality categorization. In conclusion, Eco-Heart Index has the great potential to be a community-based water quality indicator that could be understood through the universal symbol of peace and love.